2006
DOI: 10.1055/s-2007-964997
|View full text |Cite
|
Sign up to set email alerts
|

Deficit in Memory Consolidation (Abnormal Forgetting Rate) in Childhood Temporal Lobe Epilepsy. Pre and Postoperative Long-Term Observation

Abstract: Deficits in memory consolidation have been reported in adult patients with epilepsy but, not to our knowledge, in children. We report the long-term follow-up (9 y. o. to 18 y. o.) of a boy who suffered from temporal lobe epilepsy and underwent a left temporal lobectomy with amygdalo-hippocampal resection at the age of 10. He showed an abnormal forgetting rate when trying to encode new information and a significant deficit for retrieving remote episodic memories (when compared with his twin brother), both consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…apparently demonstrated AF, including an autobiographical memory deficit according to his mother's report, about 1.5 years before his seizure disorder began at age nine. Cronel-Ohayon et al (2006) suggested that J.E. 's documented AF for test stimuli paired with his retrograde memory deficit suggests the presence of a consolidation deficit and, consistent with McClelland et al (1995), that there are distinct subsystems with different timeframes within the consolidation process.…”
Section: Accelerated Forgetting Summarymentioning
confidence: 74%
See 2 more Smart Citations
“…apparently demonstrated AF, including an autobiographical memory deficit according to his mother's report, about 1.5 years before his seizure disorder began at age nine. Cronel-Ohayon et al (2006) suggested that J.E. 's documented AF for test stimuli paired with his retrograde memory deficit suggests the presence of a consolidation deficit and, consistent with McClelland et al (1995), that there are distinct subsystems with different timeframes within the consolidation process.…”
Section: Accelerated Forgetting Summarymentioning
confidence: 74%
“…This slowly developing form of amnesia, dubbed long term amnesia (Kapur 1996) or accelerated forgetting (AF), does not simply constitute a mild form of the classical global amnesia syndrome (Mayes et al 2003). Five case studies have described AF over extended delays in patients with TLE (Cronel-Ohayon et al 2006;Holdstock et al 2002;Kapur et al 1997;Lucchelli and Spinnler 1998;O'Connor et al 1997;see also De Renzi and Lucchelli 1994). There also are seven group studies that examined memory after long delays in adult TLE patients (Bell 2006;Bell et al 2005;Blake et al 2000;Giovagnoli et al 1995;Helmstaedter et al 1998;Mameniskiene et al 2006;Martin et al 1991).…”
Section: Accelerated Forgettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies did not report learning performance (Dewar, Hoefeijzers, Zeman, Butler, & Della Sala, 2015;Gallassi et al, 2011;Hoefeijzers, Dewar, Dalla Sala, Butler, & Zeman, 2014;Jansari, Davis, McGibbon, Firminger, & Kapur, 2010;Lah, Mohamed, Thayer, Miller, & Diamond, 2014;McGibbon & Jansari, 2013;Narayanan et al, 2012;O'Connor, Sieggreen, Ahern, Schomer, & Mesulam, 1997;Ricci, Mohamed, Savage, Boserio, & Miller, 2015;Tramoni et al, 2011). In others, learning performance was not equated (Bell, 2006;Bell, Fine, Dow, Seidenberg, & Hermann, 2005;Cronel-Ohayon et al, 2006;Giovagnoli, Casazza, & Avanzini, 1995;Holdstock, Mayes, Isaac, Gong, & Roberts, 2002;Lucchelli & Spinnler, 1998;Mameniskiene et al, 2006;Mayes et al, 2003). These omissions or oversights limit the implications of these studies, as the role of subtle acquisition deficits cannot be excluded.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Yet, there is evidence that both short-term working memory and long-term reference memory can be impaired in patients with hippocampal damage (Abrahams et al, 1999). Indeed, recent animal research has gone further in suggesting that the two types of memory can be dissociated (Sanderson et al, 2009;Rust et al, 2010), and the epilepsy literature is increasingly showing an inability to retain learned memories over a long period of time, a phenomenon referred to as accelerated forgetting (Blake et al, 2000;Cronel-Ohayon et al, 2006;Bell and Giovagnoli, 2007;). …”
Section: Introductionmentioning
confidence: 99%